Negotiating Dual Identities: A Case Study on The Narratives of Two Myanmar Refugee Youths Living in Malaysia - Charity Lee (Kajian Malaysia, 2020)
This article explores the experiences of two Myanmar refugee youths, who were born and raised in Malaysia – Prince, a Rohingya boy and John, a Burmese boy – through their narratives on belonging and identity and Gee’s framework for identity analysis. Selected excerpts from the respondents’ narratives were analysed using positioning analysis. A salient aspect in the narratives of both respondents was agency to choose for themselves identities that would enable them to achieve particular goals. The narratives presented here revealed a complex weaving of two main identities: Malaysian and refugee. The analysis revealed how the respondents often chose to downplay aspects of their refugee-ness to take up a Malaysian identity, with both identities functioning as binary identities. However at other times, they also attempted to merge both into a dual or hybrid identity, illustrating that identity work involves overlapping aspects of refugee subjectivities that sometimes contradict each other. The article ends with some recommendations for more inclusive policies for refugees in Malaysia, including crafting legislation that acknowledges refugees and allowing them formal access to learning local languages and integrating with local communities.